UPAYA MENINGKATKAN KETERAMPILAN MEMBACA CEPAT MELALUI LATIHAN MEMBACA BERULANG (REPEATING READING) DI KELAS VI SEKOLAH DASAR - Nurhasanah, Siti; Nurasiah, Iis; Uswatun, Din Azwar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study was to improve the speed reading skills of sixth grade elementary school students through the use of the repeated reading method. The subjects of the study were six sixth grade students. The research method used was classroom action research. Data were collected through observation and testing, then analyzed using descriptive statistical techniques. The results of the study showed that in the pre-cycle, 33.33% of students fell into the very poor category, which then increased to 50% falling into the poor category. In cycle II, it increased again to 83.3% in the good category. The average score in the pre-cycle was 58.33, then increased to 73.3 in cycle I and increased again to 83.3 in cycle II. It can be concluded that the use of the repeated reading method can improve the speed reading skills of sixth-grade elementary school students